1997
DOI: 10.4141/a96-141
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with chromium picolinate reduces the incidence of placental retention in dairy cows

Abstract: . 1997. Supplementation with chromium picolinate reduces the incidence of placental retention in dairy cows. Can. J. Anim. Sci. 77: 329-330. A test with two groups (n for each group = 25) of Holstein cows was conducted to evaluate the effects of chromium picolinate (CrPic) on the incidence of placenta retention (PR). Organic chromium supplementation, equivalent to 3.5 mg Cr d -1 per cow, administered during the last 9 wk of pregnancy, decreased nearly four times the incidence of placental retention observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…They were also comparable with that of Rogosic et al (2006) who reported CP values of leaves and twigs of some Mediterranean maquis shrubs Imoro 61 ranged from 4.9 to 7.8%. The results were also in conformity with the observation by Villalobos et al (1997) and Patterson et al (2003) that nutrient deficiencies in a cow are more probable in fall and winter when nutrient contents of the grazed forages are low.…”
Section: Mean Proximate Compositionsupporting
confidence: 90%
“…They were also comparable with that of Rogosic et al (2006) who reported CP values of leaves and twigs of some Mediterranean maquis shrubs Imoro 61 ranged from 4.9 to 7.8%. The results were also in conformity with the observation by Villalobos et al (1997) and Patterson et al (2003) that nutrient deficiencies in a cow are more probable in fall and winter when nutrient contents of the grazed forages are low.…”
Section: Mean Proximate Compositionsupporting
confidence: 90%
“…The issues of reproduction in relation to Cr supplementation in cattle have been devoted relatively little attention. Despite this, a positive effect of Cr supplementation on the insemination index, interval and service period has been established (Bonomi et al, 1997;Pechova et al, 2003) as well as a reduced incidence of endometritis and placental retention (Chang et al, 1996;Villalobos et al, 1997). Bryan et al (2004) studied the effect of supplementing 6.25 mg/day of Cr from Cr methionine on lactation and reproduction in intensively grazed cattle.…”
Section: Reproductionmentioning
confidence: 99%
“…Similar results were reported also by Chang et al (1996) who did not observe any effects of Cr supplementation on the prevalence of mastitis, oedema, or abomasal displacement and found only a somewhat lower prevalence of retained placenta and endometritis in the treated cows. On the other hand, Villalobos et al (1997), who started Cr supplementation nine weeks before the expected delivery date, reported a decrease in the prevalence of retained placenta to almost one fourth of the value observed in untreated cows.…”
mentioning
confidence: 96%